DUAL UZAYDA RİBBON ÇATIYA GÖRE FOKAL EĞRİLER - TURĞUT, SEZAİ (Fırat Üniveristesi, 2021)
Öklid uzayında eğriler teorisinde farklı çatılara göre birçok çalışma yapılmıştır. Birçok bilim adamı bu teoride Frenet çatı, Bishop çatı, Adapted çatı, Ribbon çatı gibi çatıları çalışmıştır. Bu çatılar eğriler ile ilgili karakterizasyonlarda bize yardımcı olur. Bu tez çalışmasında, ilk olarak çalışmanın temelini oluşturan dual uzay ile ilgili ayrıntılı bilgilere yer verilmiştir. Daha sonra oluşturulan bu içerik kullanılarak Dual Uzayda Fokal Eğriler tanımlandı. Son olarak da Dual Uzayda Ribbon Çatı ifade edilerek bu çatıya göre Dual Fokal Eğri ifade edildi.

Many studies have been carried out according to different frameworks in the theory of curves in Euclidean space. Many scientists have studied roofs such as Frenet roof, Bishop roof, Adapted roof, Ribbon roof in this theory. These frameworks help us with characterizations about curves. In this thesis, first of all detailed information about dual the Dual space, which forms the basis of the study, is given. Using this created content later, Focal Curves in Dual Space were defined. Finally, by expressing the Ribbon roof in Dual Space, the dual Focal Curves was expresswd according to this framework.
Focal curves according to ribbon roof in dual space
Keywords: Matematik